The Effect of Interactive e-Module Learning Media Based on the Canva Application on the Discovery Learning Model on the Motivation and Learning Outcomes of Class XI MIPA Students of SMAN 7 Bulukumba (Study on Basic Material of Acid-Base Solutions) - Hamdjah, Afdhalifayanti; Alimin, Alimin; Sudding, Sudding (Jurusan Kimia FMIPA UNM, 2024)
ABSTRAK Penelitian eksperimen semu ini bertujuan untuk mengetahui pengaruh media pembelajran e-Modul interaktif berbasis canva pada model discovery learning terhadap motivasi dan hasil belajar peserta didik kelas XI MIPA SMA Negeri 7 Bulukumba tahun pelajaran 2022/2023 pada materi pokok larutan asam basa. Populasi penelitian adalah peserta didik kelas XI MIPA SMA Negeri 7 Bulukumba yang terdiri dari dua kelas, sedangan sampelnya masing-masing kelas XI MIPA 2 sebagai kelompok eksperimen dan kelas XI MIPA 1 kelompok kontrol. Variabel bebas adalah media pembelajaran e-Modul interaktif berbasis aplikasi canva pada model discovery learning dan model discovery learning tanpa media pembelajaran e-Modul berbasis aplikasi canva, sedangkan variabel terikatnya adalah motivasi dan hasil belajar peserta didik dari materi pokok larutan asam basa. Pengambilan data dilakukan dengan pemberian angket dan tes hasil belajar. Berhubung salah satu data tidak terdistribusi normal, maka uji hipotesis menggunakan uji non parametrik, hasilnya menunjukkan ada pengaruh media e-Modul interaktif berbasis aplikasi canva pada model discovery learning terhadap motivasi dan hasil belajar peserta didik. ABSTRACT This quasi-experimental study aims to determine the effect of Canva-based interactive e-Module learning media on the discovery learning model on the motivation and learning outcomes of students in class XI MIPA SMA Negeri 7 Bulukumba for the 2022/2023 academic year on the subject matter of acid-base solutions. The study population was students of class XI MIPA SMA Negeri 7 Bulukumba consisting of two classes, while the samples were class XI MIPA 2 as the experimental group and class XI MIPA 1 as tphe control group. The independent variable is the Canva application-based interactive e-Module learning media in the discovery learning model and the discovery learning model without the Canva application-based e-Module learning media, while the dependent variable is student motivation and learning outcomes from the subject matter of acid-base solutions. Data collection was carried out by giving questionnaires and learning achievement tests. Since one of the data is not normally distributed, the hypothesis uses a non-parametric test, the results show that there is an influence of interactive e-Module media based on the Canva application on the discovery learning model on motivation and learning outcomes of class.